2005
DOI: 10.1097/01.aids.0000192090.61753.d4
|View full text |Cite
|
Sign up to set email alerts
|

HIV/hepatitis C virus co-infection in drug users: risk behavior and prevention

Abstract: Studies of HIV-positive patients have consistently shown that drug users, in particular injection drug users (IDU), are far more likely to have hepatitis C virus (HCV) infection than other patient groups. HIV incidence and prevalence in IDU has declined in recent years, but HCV remains endemic in this population. HCV antibody prevalence among non-injection users of drugs such as heroin and cocaine is between 5 and 30%, although there are scant data on specific transmission risk behavior. The control of HIV/HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 84 publications
5
41
1
Order By: Relevance
“…During the year of 2006, the perinatal HIV transmission rate in the cohort of 600 (9 cases were out of state residents) HIV exposed birth events followed was 1.7 %. Maternal age of 35 years or older and IDU were the strongest predictors of HCV seropositivity, consistent with the existing body of research [16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During the year of 2006, the perinatal HIV transmission rate in the cohort of 600 (9 cases were out of state residents) HIV exposed birth events followed was 1.7 %. Maternal age of 35 years or older and IDU were the strongest predictors of HCV seropositivity, consistent with the existing body of research [16].…”
Section: Discussionsupporting
confidence: 87%
“…Both HCV and HIV are readily transmitted through injection-drug use, and about one-fourth of all HIV patients are also coinfected with HCV [15,16]. This unique statewide population-based study of a cohort of HIV-infected childbearing women showed HCV seroprevalence of 3.8 %.…”
Section: Discussionmentioning
confidence: 75%
“…Although such a protective response is difficult to evaluate in humans, two reports have demonstrated that high-risk IDUs who have already resolved one HCV infection are less likely to be reinfected than individuals who are HCV naïve, despite repeated high-risk exposures (21,38). IDUs currently represent the main reservoir of HCV (2,23). Although this group represents a major public health hazard, they have limited access to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 In HIV-infected individuals, untreated acute HCV typically progresses to chronic HCV, a leading cause of non-AIDS-related morbidity and mortality for HIV-infected persons in the highly active antiretroviral therapy (HAART) era. 9 In addition to classic risk factors for acute HCV among HIV-infected women and heterosexual men, reported risk factors among HIV-infected MSM include traumatic sexual practices (e.g., unprotected anal intercourse, use of sex toys, digital-manual insertion), and having a history of or concurrent STI.…”
Section: Introductionmentioning
confidence: 99%